STD1 (MSN3) interacts directly with the TATA-binding protein and modulates transcription of the SUC2 gene of Saccharomyces cerevisiae. - Tillman, T S (1995)
STD1 (MSN3) was isolated independently as a multicopy suppressor of mutations in the TATA-binding protein and in SNF4, suggesting that STD1 might couple the SNF1 kinase signaling pathway to the transcriptional machinery. We report here a direct physical interaction between STD1 and the TATA-binding protein (TBP), observed in vivo by the two-hybrid system and in vitro by binding studies. STD1 bound both native TBP in yeast cell-free extracts and purified recombinant TBP. This interaction was altered when TBP delta 57 was used, suggesting a role for the non-conserved N-terminal domain of TBP in mediating protein-protein interactions. We also show that perturbation of STD1-TBP stoichiometry alters SUC2 expression in vivo and that this effect is dependent on the N-terminal domain of TBP. The activation of SUC2 expression by increased copy number of STD1 occurs at the level of mRNA accumulation and it requires the same TATA element and uses the same transcription start site as does activation of SUC2 by glucose limitation. Taken together, these results suggest that STD1 modulates SUC2 transcription through direct interactions with TBP.